STRATEGI PEMETAAN KELAS BERBASIS INTEGRASI AKADEMIK DAN KEAGAMAAN UNTUK SISWA BARU DI SEKOLAH MENENGAH ISLAM - Fathia Hanifah; Nasrul Syakur Chaniago (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study aims to analysis the classroom mapping process for new students as a strategy to create a conducive, inclusive, and effective learning environment. The process considers not only academic ability but also students’ social, emotional, and Quran reading and memorization skills—reflecting the integration of general and religious education values. This descriptive qualitative study employed in-depth interviews, document analysis, and observation. Informants included the principal, vice principal for curriculum, and teachers directly involved in the mapping process. Findings show that classroom mapping is conducted collaboratively and regularly. A key strength of the school is the inclusion of Quran reading and memorization assessments as part of the criteria. This approach not only ensures more accurate class placement but also serves as a foundation for designing teaching strategies that are tailored to the individual needs and potential of each student.